Reducing caesarean delivery: An economic evaluation of routine induction of labour at 39 weeks in low‐risk nulliparous women. Issue 1 (29th December 2019) - Callander, Emily J.; Creedy, Debra K.; Gamble, Jenny; Fox, Haylee; Toohill, Jocelyn; Sneddon, Anne; Ellwood, David
Abstract: Background: Clinical interventions known to reduce the risk of caesarean delivery include routine induction of labour at 39 weeks, caseload midwifery and chart audit, but they have not been compared for cost‐effectiveness. Objective: To assesses the cost‐effectiveness of three different interventions known to reduce caesarean delivery rates compared to standard care; and conduct a budget impact analysis. Methods: A Markov microsimulation model was constructed to compare the costs and outcomes produced by the different interventions. Costs included all costs to the health system, and outcomes were quality‐adjusted life years (QALY) gained. A budget impact analysis was undertaken using this model to quantify the costs (in Australian dollars) over three years for government health system funders. Results: All interventions, plus standard care, produced similar health outcomes (mean of 1.84 QALYs gained over 105 weeks). Caseload midwifery was the lowest cost option at $15 587 (95% confidence interval [CI] 15 269, 15 905), followed by routine induction of labour ($16 257, 95% CI 15 989, 16 536), and chart audit ($16 325, 95% CI 15 979, 16 671). All produced lower costs on average than standard care ($16 905, 95% CI 16 551, 17 259). Caseload midwifery would produce the greatest savings of $172.6 million over three years if implemented for all low‐risk nulliparous women in Australia. Conclusions: Caseload midwifery presents the best value for reducing caesarean delivery rates of the options considered. Routine induction of labour at 39 weeks and chart audit would also reduce costs compared to standard care.